2014
DOI: 10.1371/journal.pone.0088390
|View full text |Cite
|
Sign up to set email alerts
|

Differential In Vitro Inhibition of Thrombin Generation by Anticoagulant Drugs in Plasma from Patients with Cirrhosis

Abstract: BackgroundTreatment and prevention of thrombotic complications is frequently required in patients with cirrhosis. However anticoagulant therapy is often withheld from these patients, because of the perceived bleeding diathesis. As a result of the limited clinical experience, the anticoagulant of choice for the various indications is still not known.ObjectivesWe evaluated the in vitro effect of clinically approved anticoagulant drugs in plasma from patients with cirrhosis.Patients/MethodsThirty patients with ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 24 publications
6
81
0
1
Order By: Relevance
“…Dabigatran is an oral direct thrombin inhibitor; no differences in coagulation markers were observed after its administration between healthy controls and patients with Child-Pugh B cirrhosis (Stangier et al, 2008), but its in vitro anticoagulant effect has been demonstrated to increase with increasing severity of liver disease (Potze et al, 2014). No clinical trials to date have used it in chronic liver disease patients.…”
Section: How Safe Is Anticoagulation Therapy To Use In Those With Chrmentioning
confidence: 99%
See 1 more Smart Citation
“…Dabigatran is an oral direct thrombin inhibitor; no differences in coagulation markers were observed after its administration between healthy controls and patients with Child-Pugh B cirrhosis (Stangier et al, 2008), but its in vitro anticoagulant effect has been demonstrated to increase with increasing severity of liver disease (Potze et al, 2014). No clinical trials to date have used it in chronic liver disease patients.…”
Section: How Safe Is Anticoagulation Therapy To Use In Those With Chrmentioning
confidence: 99%
“…• In vitro data suggest that cirrhotics may have much increased sensitivity to the anticoagulant effect of dabigatran (Potze et al, 2014) Idarucizumab (Pollack et al, 2015).…”
Section: Dabigatranmentioning
confidence: 99%
“…4 We recently showed altered in vitro potency of different anticoagulant drugs in patients with cirrhosis, compared to patients with intact liver function. 5 A theoretical risk for excessive anticoagulation when using these drugs in patients with cirrhosis and concomitant alterations in their hemostatic system exists.…”
Section: Decreased In Vitro Anticoagulant Potency Of Rivaroxaban and mentioning
confidence: 99%
“…However, we would like to emphasize recent reports advancing a more cautionary tone concerning in vitro efficacy and safety of these medications. 3,4 Cirrhosis patients are typically excluded from clinical trials assessing anticoagulants and clinicians are often left to extrapolate when developing treatment plans in this challenging population. While our series is small and no significant bleeding occurred, there is certainly risk when using these new agents, as the ability to monitor and rescue from bleeding is currently limited.…”
Section: Treating Thrombosis In Cirrhosis Patients With New Oral Agenmentioning
confidence: 99%